Efecto de la Adición de Pasta de Semillas de Sambo (cucurbita ficifolia) como reemplazo parcial de Grasa Animal en la Elaboración de Salchicha Cabanossi. - Quiñonez Ortiz, Mayte Juraniz (2019)
The objective of this research work was to evaluate the effect of sambo seed paste addition (Cucurbita ficifolia) as partial replacement of animal fat in Cabanossi sausage preparation, focusing on saturated fat decreasing, the research was carried out at Meat Industry of Agroindustrial Engineering Researching Laboratory, where the product was made from a mixture of pork, beef, animal fat and sambo seed paste (Cucurbita ficifolia), which were used more extend in formulation. For this work a completely randomized designing (DCA) with factorial arrangement A × B with three repetitions was proposed, factor A with 3 levels (percentages of sambo seed paste) 60%, 40% and 20% and factor B (types of smoked) cold smoked (20 ° C / 1hour) and hot smoked (70 ° C / 30min), giving a total of 6 treatments to evaluate. A physicochemical characterization of sambo seed paste (Cucurbita ficifolia) was carried out to determine fat, protein, total carbohydrates, moisture, ash and fiber percentage. The best treatment was determined by a physicochemical analysis of 4 variables pH, acidity, humidity and ash, which was t1 (a1b1), corresponding to 60% of sambo seed paste (Cucurbita ficifolia) in cold smoking (20 ° C / 1hour). A sensory analysis was carried out with the helping of 30 8th cycle students of the Agroindustrial Engineering career through tastings where the parameters to evaluate were color, aroma, flavor, texture, acceptability, with treatment being more accepted by tasters 1 (a1b1), in turn, a microbiological and nutritional analysis was performed, which were compared in accordance with INEN 1338-2012 standards and with a control. The cost of the product (P.V.P) for a 500g presentation was $ 1.86, a value accessible to the consumer